Impact of China's Vaccine Incidents on the Operational Efficiency of Biopharmaceutical Companies - Chai, Kuang-Cheng; Tao, Ran; Chang, Ke-Chiun; Yang, Yang (Frontiers in Public Health, 2020)
Objectives: This study aims at: (1) analyzing the 15 representative biopharmaceutical companies in China before and after the vaccine incidents during the transition period of China’s economy, using financial indicators as a proxy for corporate operational efficiency and corporate social responsibility (CSR); (2) analyzing the factors influencing business operational efficiency, and providing a future development strategy for the pharmaceutical industry to better fulfill its social responsibility by studying the relationship between business operational efficiency and social responsibility performance; (3) conducting a comprehensive analysis of the results of this study, and providing relevant recommendations for biopharmaceutical companies to fulfill their social responsibilities and ensure a high quality of products. Methods and Data: The panel data regression evaluates whether a biopharmaceutical company’s social responsibility has an impact on its operational efficiency. A part of the data used in this study is obtained from the quarterly and annual financial statements of biopharmaceutical companies, while other relevant data are obtained from the China Stock Market & Accounting Research (CSMAR) database. Results: A comprehensive regression analysis of the rate of return on total assets shows that the vaccine incidents has made biopharmaceutical companies pay more attention to CSR, as actively taking social responsibility will help establish a better corporate image and form, and increase the operating efficiency. Conclusion: According to the current state of development in China, the size of a company has a positive impact on the improvement of its social responsibility and operational efficiency. The larger the company, the more attention it pays to shareholders and consumers, and the stronger its sense of responsibility to employees and society. By actively undertaking CSR activities, a company will get more support from shareholders, employees, and consumers, and will also enhance the corporate reputation. Biopharmaceutical companies actively undertake social responsibilities toward the government, employees, and shareholders, which will, to some extent, increase the public's trust in drug safety and have different degrees of impact on the overall efficiency of the company.